Biographical sketches of a late dictator. Obituaries, editorials and public statements about Franco in Great Britain and the United States. - Andrade, Juan (Historia y Comunicación Social, 2018)
This article analyzes the public declarations and the biographical sketches of Francisco Franco elaborated in Great Britain and United States of America at the moment of his death. This article pays special attention to the game of mirrors between countries and the resignification of memories about the dictator in those days. It does so by linking the published about Franco with several levels: the political and intellectual context of Great Britain and United States, the stereotypes about Spain, the myths built by the dictatorship and the historiographical production about the subject. The newspapers analyzed are, from Great Britain, The Times and The Sunday Times, The Daily Telegraph, Daily Mail and The Guardian and, from United States, The New York Times, Wall Street Journal, Los Angeles Times, Chicago Tribune and The Washington Post.